High‐Performance Solid‐State Supercapacitors and Microsupercapacitors Derived from Printable Graphene Inks. Issue 20 (21st July 2016) - Li, Lei; Secor, Ethan B.; Chen, Kan‐Sheng; Zhu, Jian; Liu, Xiaolong; Gao, Theodore Z.; Seo, Jung‐Woo T.; Zhao, Yichao; Hersam, Mark C.
Abstract : Solid‐state supercapacitors and microsupercapacitors are fabricated from a pristine graphene ink by solution casting and inkjet printing. The devices exhibit high performance, with a volumetric device capacitance up to 17.8 F cm −3 . With a simple fabrication process and robust tolerance to mechanical deformation, this work represents a promising technology for low‐cost, portable, and flexible energy storage.